Produktivitas Kakao dan Keanekaragaman Tanaman dalam Berbagai Sistem Agroforestry Berbasis Kakao di Kabupaten Pasaman Sumatera Barat - Sumilia Lia (Balai Litbang Teknologi Agroforestry, Ciamis, 2019)
In Sumatra, cocoa has been cultivated by smallholders in diverse agroforestry systems. But recently, companion shade trees are being removed in hopes of reaching higher cocoa yield. This study tests a hypothesis, that high cocoa productivity is compatible with shade and diversity if farmers apply good cocoa management. The study was conducted throughout 2018 in Sontang village, Pasaman district, West Sumatra. We aimed to compare cocoa yield and tree diversity in 3 shade management systems (low/medium/high). Twelve 20 x 20 m plots were sampled randomly under each shade, resulting in 36 plots covering 1.44 ha. Cocoa yield was assessed 6 times during the year. Plant diversity was measured by species inventories. The highest yield of dry beans was found in the simple agroforestry (596 kg ha−1), followed by low shade (400 kg ha−1) and high shade (397 kg ha−1. A laboratory analysis revealed that variation in nutrient content of litter fall might be responsible for yield differences. The medium shade also showed the highest crop diversity and highest usefulness. The study concludes that the medium shade harbors suitable level of tree diversity with a positive impact on cocoa yield. We recommend training farmers in cocoa management while sustaining medium shade as a productive, useful and bio diverse system.